The Phenomenon of Fear of Missing Out (FOMO) in the Formation of a Healthy Lifestyle and Social Identity of Golerun Running Club Members - Lia Amalia Supandi; Khaerudin Imawan; Leni Rohida (Journal of Social Science, 2026)
This study aims to analyze the role of FOMO in the running community, describe the process of forming social identity through membership, interaction, and shared activities, and interpret its relevance in influencing the way members interpret their involvement, both as an effort to maintain health and as a need for social recognition and existence. The study used a descriptive qualitative method with in-depth interview techniques with six informants, participatory observation, and documentation. The results of the study show that there is a shift in the meaning of FOMO to "Good FOMO" which plays a role in disciplining health behaviors, especially related to sleep patterns and smoking cessation. The formation of social identity emerges through the categorization of the self as an inclusive group, the internalization of the role of the "runner" in the concept of self, and social comparison through digital media that encourages motivation to achieve. The research also found a paradox of participation, namely the involvement of members more driven by the need for social existence, making physical health a by-product. It is concluded that in hybrid communities, FOMO serves as an informal social control mechanism that maintains adherence to a healthy lifestyle while strengthening the group's social identity.